Iran’s Policy towards Jewish Iranians and the State of Israel Is the Present Iranian State Islamofascist? - Amirpur, Katajun 1971- (2012)
Ever since his inauguration in 2005, Iranian president Maḥmūd Aḥmadīnezhād keeps the world on its toes with his attacks against Israel. One could easily come to the conclusion that anti-Semitism and a hostile attitude towards Jews are deeply rooted in Iranian society. Moreover one could assume that the present Iranian state has to be called Islamofascist. To come to a sounder judgment, this article looks at the situation of the Jewish Iranians—present and past—and asks how the different regimes, before as well as after the revolution, treated the Jewish minority. Iran counting today some 25,000 Jews harbors the biggest Jewish community in the Middle East with the evident exception of the State of Israel.
Keywords: Iran -- anti-Semitism -- anti-Zionism -- Aḥmadīnezhād -- Jewish Iranians